Symbolic Figures of Speech in the Lyrics of the Song Kolam Susu by Koes Plus - Yesi Fitria; Annisa Putri Andini; Bunga Ivanny Marsya; Karlia Marhamatur Robaaniyya; Encep Kusumah (Raja Zulkarnain Education Foundation, 2025)
Koes Plus is a music band that was once established in Indonesia which was formed in 1969, this music group is widely known as one of the pioneers of pop and rock and roll genre songs in Indonesia, as well as one of the most productive and longest-standing music groups.